Brassica trichocarpa (Brassicaceae), a new species from Sicily - Brullo, Cristian; Brullo, Salvatore; Galdo, Gianpietro Giusso Del; Ilardi, Vincenzo (Phytotaxa, 2013)
A new species of Brassica from Sicily, namely B. trichocarpa, is described and illustrated. This suffrutex was found on a calcareous peak of a mount near Palermo, where it is represented by a single population occupying a really small surface. It is well differentiated from the other perennial species belonging to B. sect. Brassica mainly in having hairy ovary and very short, thickened, hairy, not torulose fruits. Its relationships and taxonomical position within this group are examined too. An analytical key of the current taxa belonging to the genus Brassica sect. Brassica is also provided.